The Effect of Presence of Blood on Medical Laypeople's Ability to Perform First Aid for Massive Bleeding. (September 2022) - Brodin, Wilhelm; Friberg, Marc; Jonson, Carl-Oscar; Prytz, Erik
There are currently several educational initiatives to teach first aid courses for medical laypeople, such as the Stop the Bleed campaign. Although much research on educational initiatives has been conducted, there are still factors that remain unexplored, such as the potential effects of blood itself on laypeople's first aid performance and educational experience. This study investigates such potential effects for performance of the first aid techniques tourniquet application and wound packing, in relation to individual differences in disgust sensitivity and medical fear of blood. The results show that the presence of blood will increase the time a medical layperson takes to apply a tourniquet and pack a wound but does not affect the quality of the aid. Additionally, the disgust sensitivity of the medical layperson was found to predict an increase in application time for the wound packing task, but not the tourniquet application task, when blood was present.